Analisis Kinerja Sektor Informasi dan Komunikasi Selama Pandemi Covid-19 di Jawa Tengah: Universitas Muhammadiyah Surakarta - Tri Wahyu Ari Hastuti (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2022)
The spread of Covid-19 virus outbreak in Indonesia brings bad risks to the country's economy, including the regional economy, especially in the information and communication sector. The purpose of this study is to analyze the performance of the information and communication sector during the Covid-19 pandemic in Central Java for the period of the first quarter of 2020 to the second quarter of 2021. The method used in this study is input output analysis. The type of data used in this research is secondary data and the data collection technique used is library technique. The results of the study explain that the information and communication sector during the pandemic did not experience negative fluctuations in the economy of Central Java. However, there is a negative impact on the decline in the value of changes in household income in the information and communication sector.